Seroepidemiology of Toxoplasmosis Among HIV-Infected Patients and Healthy Blood Donors - Nissapatorn, V.; Kamarulzaman, A.; Init, I.; Tan, L.H.; Rohela, M.; Norliza, A.; Chan, L.L.; Latt, H.M.; Khairul Anuar, A.; Quek, K.F. (2002)
A cross-sectional study was carried out in University of Malaya Medical Centre, Kuala Lumpur. Blood samples from 100 HIV-infected patients and 203 Healthy Blood Donors (HBD) were collected and anti- antibodies were detected by using conventional ELISA. The seroprevalence of toxoplasmosis in HIV/AIDS and Healthy Blood Donors were found to be 21% and 28.1% respectively. There was no significant association between the seroprevalence of toxoplasmosis and various possible risk factors i.e. contact with cat, consumption of undercooked meat and history of blood transfusion in both groups. No significant differences between seroprevalence in HIV/AIDS and Health Blood Donors in association with presence of single or multiple risk factors were found. The mean CD4 count among HIV/AIDS patients in this study was 202.23 cell/cumm. There was no significant association between CD4 count and seropositivity for antibodies in HIV/AIDS patients.